TAX REFORM AND NONCOMPLIANCE IN INDONESIA - Heru Iswahyudi (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
The purpose of this paper is to examine the impact of Indonesia’s tax reforms of 2000 and 2008/2009 on taxpayers’ noncompliance. Noncompliance is defined as the difference between the Value Added Tax (VAT) liability and the actual revenue. Data are mainly collected from the World Input-Output Database and Indonesia’s Central Board of Statistics. The methodology uses one of the ‘top-down’ approaches, in which national accounts figures are employed to arrive at an estimation of the VAT liability. It is found that compliance deteriorated when reform efforts were incomplete – that is when the reforms suffered from decelerations, setbacks or reversals. This paper contributes to the literature by providing a framework for analyzing the impact of tax reform on taxpayer’s compliance behavior.